Empreendedorismo na formação de professores: uma proposta formativa - Barros, Marcus Marcelo Silva (2017)
The referent study entitled "Entrepreneurship in teacher training: a formative proposal" is the result of research conducted in the MPET of the Federal Institute of Education, Science and Technology of Amazonas (IFAM), whose interest originated from the relation between entrepreneurship and education, has led to the search for understanding teachers' positions regarding the importance of entrepreneurship as a strategy for teacher training, in view of a professional who daily expends efforts to prepare citizens to meet and respond to the demands demanded by the world of work . For the development of the study, it was necessary, in the first moment, to adopt a theoretical perspective based on the formation of teachers, their approaches and unfolding. In a second moment, it was about entrepreneurship, its trajectory, entrepreneurial characteristics and its applicability in the educational context. As to the fundamentals and execution of the methodological course, the research was of mixed nature (quantitative / qualitative), through the exploratory research, using as an instrument, for the data collection, questionnaire and interview. The collected data were treated by Discursive Textual Analysis - ATD. As subjects of this study, teachers of the Federal Institute of Education, Science and Technology of Acre - IFAC, who work in the Rio Branco Campus, were surveyed. The results obtained through the ATD process indicated: how the researched teachers identify, relate and conceptualize the term entrepreneurship in front of their experiences and family trajectory; the importance and influence of teacher educators who have used innovative and contextualized forms of teaching in the classroom, contributing significantly to their training process; and the need to provide an entrepreneurial environment in the institution, so as to create and foster an entrepreneurial culture, configuring itself as an educational strategy. As a result of the results and contestations, a product was created entitled: entrepreneurship refresher course for teachers, as a contribution to the training process of teachers. Finally, it is expected that our research will promote and encourage debates, reflections and discussions about the applicability of entrepreneurship in the educational context, especially in teacher training.